Lower Ordovician (Billingenian - Kunda) conodont zonation and provinces based on sections from Horns Udde, north Öland, Sweden - BAGNOLI, GABRIELLA; Stouge S. (1996)
The Hunnebergian to Kunda conodont succession of the lower Ordovician Orthoceras Limestone on northern Öland, Sweden is described. The faunal succession is based on 57563 conodont elements recorded from two representative sections: North of Horns Udde and Horns Udde quarry. The new data allow the recognition and definition of 10 successive interval zones, each characterized by a nominate species and a distinctive conodont association. The interval zones are recommended to substitute the previous assemblage zones in future references to the conodonts of the Öland region. The interval zones are compared with earlier and corresponding zones of the lower Ordovician in neighbouring areas. The interval zones provide an alternative reference to former formally established zones as precise correlation across the East European Platform is possible. The fauna changed from cosmopolitan in Billingen time to provincial in Volkhov time. The fauna assemblages changed from Pandemic forms to temperate water (Precordilleran) faunas and finally were replaced by cold water (Baltic Province) conodonts of the North Atlantic Realm. The Baltic Province persisted throughout the lower Ordovician on the East European Platform. The change of fauna from Pandemic to provincial is connected with sea level changes and a shallowing of the shelf environs. One new multielement genus is recognized: Lundodus; one multielement genus has been revived: Gothodus Lindström, 1955, and two multielement genera are revised: Lenodus Sergeeva, 1963 and Trapezognathus Lindström, 1955. Four new species are named: Parapanderodus quietus, Protopanderodus floridus, Protopanderodus calceatus, and Scolopodus princeps, and 20 species are reported but not formally named because they are of low occurrences but with a known apparatus structure and because the number of specimens avaible was not adequate for their definition.